2014
DOI: 10.1002/2013jd020931
|View full text |Cite
|
Sign up to set email alerts
|

Transport from convective overshooting of the extratropical tropopause and the role of large‐scale lower stratosphere stability

Abstract: Simulations of observed convective systems with the Advanced Research Weather Research and Forecasting (ARW‐WRF) model are used to test the influence of the large‐scale lower stratosphere stability environment on the vertical extent of convective overshooting and transport above the extratropical tropopause. Three unique environments are identified (double tropopause, stratospheric intrusion, and single tropopause), and representative cases with comparable magnitudes of convective available potential energy ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 59 publications
1
55
0
Order By: Relevance
“…Figure shows that the domain‐averaged echo top in the model is largely biased low compared to observation. This result is comparable to that demonstrated in previous studies [e.g., Homeyer et al , ] and is likely due to limited representation of ice particle shapes and densities and differential sedimentation of precipitable particles in the BMP. However, the domain‐averaged cloud top is found to be 1.5–2 km higher than that observed by radar and is expected based on the limitations of the measurement, providing confidence in the representativeness of the simulated storms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows that the domain‐averaged echo top in the model is largely biased low compared to observation. This result is comparable to that demonstrated in previous studies [e.g., Homeyer et al , ] and is likely due to limited representation of ice particle shapes and densities and differential sedimentation of precipitable particles in the BMP. However, the domain‐averaged cloud top is found to be 1.5–2 km higher than that observed by radar and is expected based on the limitations of the measurement, providing confidence in the representativeness of the simulated storms.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these studies focus on individual cases of overshooting storms. Since direct measurement of convective overshoots is not possible with current research aircraft and alternative instrumentation, studies of tropopause‐penetrating convection in the extratropics with high‐resolution numerical models have also been common [e.g., Stenchikov et al , ; Gray , ; Wang , ; Mullendore et al , ; Lane and Sharman , ; Luderer et al , ; Chagnon and Gray , , ; Lane and Sharman , ; Homeyer et al , ; Bigelbach et al , ]. These modeling studies have identified important mechanisms for irreversible troposphere‐to‐stratosphere transport including gravity wave breaking and turbulent mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Problems may arise due to prescribed aerosol loads acting as condensation nuclei which do not reflect actual aerosol amounts . Homeyer et al (2014) indicate that the vertical resolution of the meteorological input fields, particularly in the UTLS, can impact the model representation of the crosstropopause transport. Also, the horizontal resolution has been shown to be an important factor in order to resolve the convective processes (Bryan et al, 2003).…”
Section: General Model Representationmentioning
confidence: 99%
“…Folkins et al, 2002;Barth et al, 2007;Pommereau, 2010;Romps and Kuang, 2010), especially in the mid-latitudes (e.g. Wang, 2003;Hegglin et al, 2004;Mullendore et al, 2005;Homeyer et al, 2014), only few studies look at the downward transport of tracers triggered by convection (Lu et al, 2000;Hu et al, 2010;Barthe et al, 2011). However, these upper-level downdrafts, which are either direct convective downdrafts or related to gravity waves, may also transport dry and ozone-rich stratospheric air across the tropopause (Lu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Vigorous turrets associated with deep convection generate intense precipitation that influences the hydrological cycle and large anvil shields that modulate radiation due to their extensive spatial and temporal coverage (Feng et al, 2011;Wang et al, 2015). Overshooting tops associated 15 with strong updrafts are responsible for stratosphere-troposphere exchange (Homeyer et al, 2014;Frey et al, 2015) and can be an indicator of a severity of thunderstorm (Proud, 2015).…”
Section: Introductionmentioning
confidence: 99%